2021
DOI: 10.1007/s00394-021-02606-z
|View full text |Cite
|
Sign up to set email alerts
|

The determinants and longitudinal changes in vitamin D status in middle-age: a Northern Finland Birth Cohort 1966 study

Abstract: Purpose Populations living in the Nordic countries are at high risk for vitamin D (VitD) deficiency or insufficiency. To reduce the risk, nationwide interventions based on food fortification and supplementation are being implemented. However, there is limited evidence about the impact of such public health campaigns on target populations. Methods We studied an unselected sample of 3650 participants (56.2% females) from the longitudinal Northern Finland Bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A larger increase in mean 25(OH)D concentrations was observed in a Finnish cross-sectional study of 10,185 individuals: from 19.2 ng/mL in 2000 to 26.0 ng/mL in 2011 52 and is mainly explained by food fortification, especially of fluid milk products and increased vitamin D supplement use. Other studies have corroborated that 25(OH)D concentrations have increased dramatically in Finland 53 . In Sweden, a large cross-sectional study between 1986 and 2014, based on data from seven population-based surveys, indicated no clear upward or downward trend of 25(OH)D concentrations 48 .…”
Section: Discussionmentioning
confidence: 77%
“…A larger increase in mean 25(OH)D concentrations was observed in a Finnish cross-sectional study of 10,185 individuals: from 19.2 ng/mL in 2000 to 26.0 ng/mL in 2011 52 and is mainly explained by food fortification, especially of fluid milk products and increased vitamin D supplement use. Other studies have corroborated that 25(OH)D concentrations have increased dramatically in Finland 53 . In Sweden, a large cross-sectional study between 1986 and 2014, based on data from seven population-based surveys, indicated no clear upward or downward trend of 25(OH)D concentrations 48 .…”
Section: Discussionmentioning
confidence: 77%
“…Because vitamin D deficiency is related to a number of diseases and premature mortality, vitamin D supplementation programmes have the potential to prevent disease and increase the life expectancy of the population of the Russian Arctic [2][3][4]. A successful programme of vitamin D supplementation in Finland might be an example to follow [21]. However, proper planning of vitamin D supplementation programmes in the Russian Arctic requires further research into vitamin D deficiency and its determinants in the population of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency has become common in indigenous populations of the Arctic in recent decades as a result of their transition to a Western diet pattern and this has been followed by an increase in cardiovascular disease, obesity, diabetes and cancer [10,18,19]. However, some countries in the Arctic have achieved substantial improvements in population health [20], including a decreasing prevalence of vitamin D deficiency [21].…”
Section: Introductionmentioning
confidence: 99%
“…Irish dietary vitamin D intakes have currently been estimated at 4.2 μg per day in adults aged 18-64 yrs old [52]. In contrast, in Finland which has a systematic policy of vitamin D food fortification of milk products and fat spreads, the proportions of vitamin D deficiency are <1% at the population level [53][54][55]. In recognition of the evidence regarding the poor dietary vitamin D intakes and inadequate vitamin D status of older Irish adults, the Food Safety Authority of Ireland has recently recommended all older Irish adults to consume a daily 15 μg/ 600 IU vitamin D supplement [6].…”
Section: Plos Onementioning
confidence: 99%